Peningkatan Kinerja Karyawan Melalui Disiplin dan Motivasi Kerja Karyawan Bank - Malomis, Edsel M.; Areros, William A.; Sambul, Sofia A. P. (Productivity, 2020)
This study intends to find out the extent of the influence of discipline and work motivation on employee performance. The object of this research is employees at PT Bank SulutGo main branch located in the city of Manado. Sampling was carried out using the formula proposed by Slovin, so the number of samples in this study were 60 employees out of a total of 150 employees as the population. By using regression analysis, the results show that discipline partially influences employee performance, so does work motivation affects employee performance. The results of the multiple regression analysis between discipline and work motivation on employee performance showed a significant effect. Through this research, it is hoped that the management of PT Bank SulutGo can continue to improve employee performance by striving to maintain, even encourage employee discipline and work motivation with a humanistic approach in accordance with the development of contemporary human resource governance.